Analyzing the Impact of Wing Flexural Axis Position on the Dynamics of a Very Flexible Airplane Using Strain-based Formulation - Marcelo Santiago de Sousa; Flávio Luiz Cardoso Ribeiro; Roberto Gil Annes da Silva; Pedro Paglione; Sebastião Simões da Cunha Junior (Archives of Current Research International, 2024)
New technologies and the needs of specific missions have allowed and stimulated the development of airplanes with great structural flexibility. In these vehicles, there is a significant coupling between aeroelastic phenomena and flight dynamics. This has been a topic of research in recent years. Different methodologies have been studied to model the complete dynamics of flexible aircraft. One of these is the NFNS_s methodology (Non linear flight dynamics, non linear structural dynamics, strain based formulation). This article presents the use of this methodology in the analysis of the aeroelastic response and flight dynamics of a transport category aircraft with high structural flexibility. The effects of the wing elastic axis and the flexural axis positions were analyzed. Trimming, calculus of eigenvalues and time-marching simulations were carried out and the results were analyzed in detail. Some results were compared with those published in the literature. Similar trends were observed. This served as a qualitative validation of the methodology used. Some limitations of the study are described. The contributions of this work lie in the use of the NFNS_s methodology to analyze the effects of the elastic and flexural axis positions. In addition, the results of time marching simulations of the airplane modeled and the analysis carried out in great detail are other important novelty.